Identification of acquired Notch3 dependency in metastatic Head and Neck Cancer - Kondratyev Maria; Pesic Aleksandra; Ketela Troy; Stickle Natalie; Beswick Christine; Shalev Zvi; Marastoni Stefano; Samadian Soroush; Dvorkin-Gheva Anna; Sayad Azin; Bashkurov Mikhail; Boasquevisque Pedro; et al. (Nature Publishing Group, 2025)
During cancer development, tumor cells acquire changes that enable them to invade surrounding tissues and seed metastasis at distant sites. These changes contribute to the aggressiveness of metastatic cancer and interfere with success of therapy. Our comprehensive analysis of "matched" pairs of HNSCC lines derived from primary tumors and corresponding metastatic sites identified several components of Notch3 signaling that are differentially expressed and/or altered in metastatic lines and confer a dependency on this pathway. These components were also shown to be differentially expressed between early and late stages of tumors in a TMA constructed from over 200 HNSCC patients. Finally, we show that suppression of Notch3 improves survival in mice in both subcutaneous and orthotopic models of metastatic HNSCC. Novel treatments targeting components of this pathway may prove effective in targeting metastatic HNSCC cells alone or in combination with conventional therapies.Analysis of matched pairs of head and neck squamous cell carcinoma (HNSCC) lines from primary and metastatic sites identifies differential expression of Notch3 components, and suppression of Notch3 improves survival in mouse models of metastatic HNSCC.